PENGARUH KEBIASAAN MINUM TEH SETELAH MAKAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS TEBING SYAHBANDAR - Putri Ayu Yessy Ariecha; Luhur Monalisa; Peny Ariani; Tetty Junita Purba; Nur Mala Sari (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Tea consumption have been mother tea eliminate and vomiting that occurs during pregnancy. Research purpose to find out The Influence Of The Habit Of Drinking Tea After Eating On The Incidence Of Anemia In Pregant Women In Puskesmas Tebing Syahbandar year 2020. The research design wan an analytical research with cross sectional approach, the sample is 32 respondents which used total sampling. The independen variable the habit of drinking tea after eating and dependent variable was the incidence of anemia. The research instruments were questionnaire. Data were analyzed by Chi-Square test with Î± < 0,05. The research result showed thst most of the 32 respondents (62,5%) tea drinking habits and the rest (40,6%) had mild anemia. Chi-Square test result showed that with the significance value of Î± = 0,05, it was obtained that the value of p = 0,003which means p < Î± so H0 was rejected, it means that there was The Influence Of The Habit Of Drinking Tea After Eating On The Incidence Of Anemia In Pregant Women In Puskesmas Tebing Syahbandar year 2020. The more frequent consumption of tea, the higher the rate of anemia in pregnant women. It is expected to the nurses to improve the counseling further to them about the importance of good and appropriate nutrition obtained from food or beverages consumed by them.